HUBUNGAN INTENSITAS PENDIDIKAN AGAMA ISLAM DENGAN PEMBENTUKAN AKHLAK SISWA DI SMP ISLAM ROUSHAN FIKR JOMBANG: HUBUNGAN INTENSITAS PENDIDIKAN AGAMA ISLAM DENGAN PEMBENTUKAN AKHLAK SISWA DI SMP ISLAM ROUSHAN FIKR JOMBANG - , Mahmud Fauzi, Wardah Thoyyibah (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: The study looked for influence between the intensity of Islamic religiouseducation on the formation of student morals at SMP Roushan Fikr Jomnbang MiddleSchool. With this type of ex-post facto research in the form of a correlation study, thisstudy produced: first, the intensity of Islamic Religious Education at Roushan FikrJombang Islamic Junior High School which was in poor level with a frequency of 38 anda percentage of 100%, in a fairly good level with a frequency of 38 and a percentage of 0%, secondly, the Formation of Morals in Roushan Fikr Jombang Islamic Junior HighSchool which is in a poor level with a frequency of 38 and a percentage of 100%, in afairly good level with a frequency of 38 and a percentage of 0%, while in a very goodlevel with a frequency of 0 and a percentage of 0%. In the analysis of spearman rank, itreads Sig. (2-tailed) = 0.082 which proves that there is no relationship between IslamicReligious Education with the formation of student morals at the Islamic Roushan FikrJombang Middle School. With the correlation coefficient figure of 0.082 which is apositive value so that the relationship between the two variables is unidirectional, thus itcan be interpreted that the increasing intensity of Islamic religious education increases theformation of morals also increasing. Or conversely, the decreasing intensity of Islamicreligious education will also decrease the formation of morals.Keywords: Intensity of Religious Education, Formation of Morals